New Protocol Avoiding Tube Feed Interruptions in Critically Ill Patients Requiring Tracheostomy. Issue 6 (June 2018) - Angotti, Lisa M.; Casey, Colleen; Ata, Ashar; Sueda, Stefanie; Ettekal, Yashar; Lee, Christina; Bonville, Daniel; Stain, Steven C.; Tafen, Marcel
Current anesthesia guidelines require tube feed (TF) interruption for at least four hours before tracheostomy. We hypothesized that preprocedural TF interruption is not required before tracheostomy. We developed a protocol allowing continued feeding. Fifty-six patients undergoing tracheostomy with or without percutaneous endoscopic gastrostomy placement were included. Eleven patients underwent tracheostomy without TF interruption (TF group); the remaining 45 patients had TFs held per the existing anesthesia protocol (nil per os group). Data were collected by retrospective chart review. The groups were similar with regard to age, sex, race, risk of mortality, and preoperative albumin levels (3.2 vs 2.9 g/dL). There was no difference in pulmonary complications. No intraoperative aspiration occurred in either group, and there was no increase in mortality in the TF group (9.1 vs 22.2%, P = 0.43). The TF group had feeds held for 9.5 ± 6.3 vs 25.4 ± 19.0 hours (P = 0.0018). The TF group had a decreased missed caloric intake [761.5 ± 566.6 vs 1983.5 ± 1590.8 kcal (P = 0.0039)]. The TF group had a shorter time from consultation [40.4 vs 50.6 hours (P = 0.54)] and case booking [7.9 vs 12.8 hours (P = 0.40)] to the OR. The average length of stay for the TF group was 26.3 versus 31.1 days (P = 0.45). There was no increase in pulmonary complications or mortality in the fed patients, who experienced less procedural delays. Meanwhile, patients kept nil per os sustained a substantial caloric deficit. Tracheostomy without TF interruption is feasible and reduces malnutrition.